A novel and improved developer rank algorithm for bug assignment. (10th February 2020) - Yadav, Asmita; Singh, Sandeep Kumar
Analytical studies on automatic bug triaging approach have the main objective to recommend appropriate developer for bug report with reduced bug tossing length, time and effort in bug resolution. In bug triaging process, if the first recommended developer cannot fix a bug, it is tossed to another developer and the tossing process is continued till the bug gets assigned and resolved. Existing approaches to the best of our knowledge have not considered developer's contributions and performance assessment metrics for bug triaging process. In this paper, we proposed a novel and improved two phase bug triager that involves a developer profile creation and assignment phases. In this, developer profile is built by using individual contributions (IC) and performance assessment (PA) metrics. Contribution and performance of a developer in pre-fixed bug reports are analysed to calculate a developer's weighted score. This score indicates the level of expertise to fix and resolve a newly reported bug. This approach is tested on two open source projects - Eclipse and Mozilla. Empirical results show that proposed approach has achieved a significantly higher F-score up to 90% for both projects and has effectively reduced bug tossing length up to 11.8% as compared to existing approaches.